Platelet secretions exert anti-inflammatory effects in vitro on neutrophils and uterine epithelia in cattle: a possible role in amplifying the uterine immune network toward pregnancy - Yousef, Mohamed Samy; Akthar, Ihshan; Ma, Dongxue; Haneda, Shingo; Kusama, Kazuya; Shimada, Masayuki; Imakawa, Kazuhiko; Miyamoto, Akio (Frontiers in Immunology, 2025)
BackgroundPlatelet derivatives improve the uterine immune environment and increase pregnancy success in humans and animals. Platelet-conditioned media (PCM) contain all molecules derived from platelets in vitro (platelet secretions). The present study aimed to investigate the immunological impacts of platelet secretions on polymorphonuclear neutrophils (PMNs) and bovine endometrial epithelial cells (BEECs), in vitro.MethodsPlatelets (10×107 platelets/mL) from Holstein dairy cows were incubated for 0.5 h or lysed to obtain the PCM and platelet lysate (Lysate), respectively. PMNs were stimulated with PCM for 3h. While BEECs were exposed to PCM or Lysate for 24 h. Real-time PCR was performed to detect the expression of targeted genes (cytokines), including TNFA, IL1B and PGES1. Lipoxin A4 (LXA4; anti-inflammatory mediator) and PGE2 concentrations in the supernatants of PMNs cultured with PCM were measured via ELISA. Cell proliferation in BEECs was assessed using the Cell Counting Kit-8 (CCK-8). Additionally, uterine explants were prepared and processed for immunofluorescence to determine the expression of the LXA4 receptor.ResultsIn PMNs, platelet secretions downregulated the mRNA expression of pro-inflammatory cytokines (TNFA and IL1B) and increased LXA4 production. In both PMNs and BEECs, platelet secretions upregulated PGES1 expression and PGE2 production. In BEECs, platelet secretions and Lysate upregulated TGFB1. While Lysate suppressed IL1B mRNA expression. Further, platelet secretions showed an anti-proliferative effect in BEECs and increased the LXA4 receptor protein expression in the endometrial epithelia.ConclusionsOur findings reveal for the first time that platelet secretions directly act on PMNs and BEECs in vitro, thereby assisting the uterine immune network to shift anti-inflammatory environment toward pregnancy. The present study can explain, in part, the successful applications of platelet derivatives in reproductive medicine.